2021
DOI: 10.3390/jcm10194551
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Management of Patients with Primary Biliary Cholangitis—A Retrospective Study from a Tertiary Medical Center in Israel

Abstract: Background: Primary biliary cholangitis (PBC) is a rare autoimmune liver disease with variation in prevalence, phenotype and prognosis across different geographical regions. Little is known about PBC in Israel. Our aim was to characterize the demography, clinical presentation, treatment patterns and prognosis in a cohort of PBC patients followed in a referral center in central Israel. Methods: Clinical, demographic and laboratory data were collected from the medical records of PBC patients followed at Tel Aviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Logically, patients who respond to registered PBC treatment can expect a better prognosis than patients who do not respond. In recent years, several studies have been published looking at the prognosis of PBC patients treated with UDCA, evaluating standard laboratory parameters prior to the initiation of PBC treatment 28 , 34 37 Chinese authors found that a low albumin level and a higher IgG level as well as all liver tests (alanine aminotransferase (ALT), AST, GGT, and ALP) before starting UDCA treatment predicted a lack of response to UDCA. 36 High ALP prior to UDCA treatment is associated with an incomplete response to treatment.…”
Section: Prognostic Aspects Of Pbc In Udca Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Logically, patients who respond to registered PBC treatment can expect a better prognosis than patients who do not respond. In recent years, several studies have been published looking at the prognosis of PBC patients treated with UDCA, evaluating standard laboratory parameters prior to the initiation of PBC treatment 28 , 34 37 Chinese authors found that a low albumin level and a higher IgG level as well as all liver tests (alanine aminotransferase (ALT), AST, GGT, and ALP) before starting UDCA treatment predicted a lack of response to UDCA. 36 High ALP prior to UDCA treatment is associated with an incomplete response to treatment.…”
Section: Prognostic Aspects Of Pbc In Udca Treatmentmentioning
confidence: 99%
“… 35 High ALP prior to UDCA treatment correlated with an inadequate response to treatment in multivariate analysis, while young age at diagnosis of PBC, presence of pruritus prior to treatment, low albumin prior to treatment, and high ALT, GGT, and ALP predicted disease progression. 37 Low AST and ALT levels prior to UDCA treatment correlate with the achievement of a biochemical response. 34 …”
Section: Prognostic Aspects Of Pbc In Udca Treatmentmentioning
confidence: 99%